The Impact of Family Income on Students Financial Attitude - Nano, Dorjana; Llukani, Teuta; Polo, Antoneta (European Journal of Economics and Business Studies, 2015)
This research explores the differences on Financial Attitudes among Albanian university students based on their family income. The main objectives of this study are: i) firstly, to assess students attitude towards money management practices; ii) to examine whether their financial attitude differs based on the level of family income; and iii) finally, to present some conclusions and recommendations for parents, practitioners and students in way that they can shape healthy financial habits. An instrument comprised of specific and personal questions is administered to 637 students from five public and two private universities in Albania. The consistency and reliability of the survey is tested by the dimension reduction technique and Cronbach Alpha test. Data analysis is conducted based on analyse of variance. The results exhibits that Albanian university students do not have good financial attitude. Parental income is found to influence their children attitude towards money issues. Students with low parental income are discovered to show better financial attitude in comparison with other categories. This research recommends parents and other practitioners to teach proactively students about money smart.